2017
DOI: 10.1111/1758-2229.12501
|View full text |Cite
|
Sign up to set email alerts
|

Non‐target effects of fungicides on nectar‐inhabiting fungi of almond flowers

Abstract: Nectar mediates interactions between plants and pollinators in natural and agricultural systems. Specialized microorganisms are common nectar inhabitants, and potentially important mediators of plant-pollinator interactions. However, their diversity and role in mediating pollination services in agricultural systems are poorly characterized. Moreover, agrochemicals are commonly applied to minimize crop damage, but may present ecological consequences for non-target organisms. Assessment of ecological risk has te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
3
36
1
Order By: Relevance
“…For habitats, diversity results were as expected, as it is well known that the organic matter in the soil is an important source of nutrients for microorganisms and contains higher levels of fungal and bacterial propagules than hydroponic systems 17 . The diversity in treatments is in agreement with a study by Schaeffer, et al 18 , which showed fungicides application on nectar have no observable effect on bacterial OTU richness or community compositions. Furthermore, higher bacterial populations observed on the immature (green) fruit surfaces compared to the mature samples corroborated with findings by Palumbo, et al 19 , who found greatest bacterial diversity on early summer mature almond fruits than on the late summer mature almonds.…”
Section: Resultssupporting
confidence: 92%
“…For habitats, diversity results were as expected, as it is well known that the organic matter in the soil is an important source of nutrients for microorganisms and contains higher levels of fungal and bacterial propagules than hydroponic systems 17 . The diversity in treatments is in agreement with a study by Schaeffer, et al 18 , which showed fungicides application on nectar have no observable effect on bacterial OTU richness or community compositions. Furthermore, higher bacterial populations observed on the immature (green) fruit surfaces compared to the mature samples corroborated with findings by Palumbo, et al 19 , who found greatest bacterial diversity on early summer mature almond fruits than on the late summer mature almonds.…”
Section: Resultssupporting
confidence: 92%
“…Another important aspect to consider is that fungicides can reduce the diversity and richness of nectar microorganisms (fungus and bacteria) in flowers, which decreases nectar quality, sugar concentration or pH, having consequences for the feeding of natural enemies [104]. Therefore, consequences of the application of fungicides on parasitoids should be further studied.…”
Section: Fungicidesmentioning
confidence: 99%
“…All evidence suggests agricultural floral nectar regularly contains floral microorganisms (13,21,22), but their effects on plant reproduction and pollination are rarely considered. Reports in the literature are mixed: in wild herb populations, the presence of yeasts increased pollen transfer in one study, but reduced seed set in another (3,6).…”
Section: Discussion Nectar Microorganisms: Opportunities For Agriculturementioning
confidence: 99%